PERLINDUNGAN HUKUM TERHADAP KONSUMEN YANG DIRUGIKAN AKIBAT PENIPUAN OLEH PT GRAB TOKO INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (KASUS: DESTY NURCAHYANI DENGAN PT GRAB TOKO INDONESIA DI TAHUN 2020) - Tamar Lidya Anggaristi P.P; Mariske Myeke Tampi (Jurnal Hukum Adigama, 2021)
The world is currently undergoing changes, where currently all use online-based information technology. Starting from learning activities, working, playing to shopping. In modern times like today, most people have switched from shopping in conventional markets to shopping online through ecommerce or marketplaces. In the midst of sophisticated technological conditions, it is possible to fulfill all needs through e-commerce, because almost all primary or secondary human needs are available in it. The advantage of transacting online is that it is easier, faster and more practical. But besides the advantages, shopping online certainly has a weakness, namely, we cannot see the goods directly before buying, the goods that have been ordered reach the consumer in a damaged condition due to online shipping expeditions, and fraud is often committed by business actors against consumers or buyers . So if there is a dispute between business actors and consumers, legal protection efforts are needed for consumers who are harmed or experience fraud with the aim of fulfilling their rights as consumers and business actors are required to carry out their obligations in accordance with applicable laws and regulations.